2010
DOI: 10.1111/j.1475-6773.2010.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High‐Deductible Health Plans on Health Care Utilization and Costs

Abstract: Background. High-deductible health plans (HDHPs) are of high interest to employers, policy makers, and insurers because of potential benefits and risks of this fundamentally new coverage model. Objective. To investigate the impact of HDHPs on health care utilization and costs in a heterogeneous group of enrollees from a variety of individual and employer-based health plans. Data. Claims and member data from a major insurer and zip code-level census data. Study Design. Retrospective difference-in-differences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…The limited published data reporting on cost-sharing mechanisms comes from the United States, where the relation between health insurance cost-sharing mechanisms, not medication insurance, is arguably different. 12,13 Our findings are particularly relevant given the current discussion in the academic literature regarding the need for a system of national pharmacare to replace the current patchwork system of pharmaceutical insurance in Canada.…”
Section: Discussionmentioning
confidence: 85%
“…The limited published data reporting on cost-sharing mechanisms comes from the United States, where the relation between health insurance cost-sharing mechanisms, not medication insurance, is arguably different. 12,13 Our findings are particularly relevant given the current discussion in the academic literature regarding the need for a system of national pharmacare to replace the current patchwork system of pharmaceutical insurance in Canada.…”
Section: Discussionmentioning
confidence: 85%
“…39,42 Three studies reported cost data with mixed results. 4345 Five studies risk-adjusted data. 39,42,45,46,48 …”
Section: Resultsmentioning
confidence: 99%
“…1–3 This is occurring in the context of widespread increases in patient cost-sharing and rapid growth in enrollment in high-deductible health plans. 2,47 Consequently, Americans have more financial ‘skin in the game’ than ever before, and 59–80% of patients want to discuss healthcare costs with their physicians. 20,4951 With nearly half of cost discussions involving cost-reducing strategies, our findings suggest that patient-physician discussion about out-of-pocket costs may be a helpful tool in addressing patients’ financial distress.…”
Section: Discussionmentioning
confidence: 99%
“…3 Key contributors to high out-of-pocket healthcare costs include increases in patient cost sharing, growth in high deductible healthcare plans, and increased use of expensive biologic or designer drugs. 2,47 In addition to depleting financial savings and damaging credit, high out-of-pocket medical costs negatively impact quality of life, medication adherence, and a variety of health outcomes. 3,6,8–12 …”
Section: Introductionmentioning
confidence: 99%